Youth Leadership Training Masjid for Performance Improvement of Youth Program Masjid Al Jihad Bandar Baru - Sebayang, Saimara AM; Diana, Yana; Harianto, Harianto (Journal of Community Research and Service, 2023)
The purpose of this community service is to carry out mosque youth leadership training to improve the performance of the Mosque youth program located at the Al-Jihad Mosque in Bandar Baru. The design of the activities carried out is training in the form of socialization to productive adolescents. The PKM activities are divided into 2 (two) stages, namely 1) the initial stage of preparation, which consists of; (a) collect data on prospective trainees who are active in the youth organization of the Bandar Baru Al-Jihad Mosque, (b) conduct discussions with all implementers discussing the results of observations that have been made, (c) prepare the necessary training equipment and materials. 2) the stage of implementation of activities, in the form of presentation materials, discussions and questions and answers as well as simulations of leadership in the organization. Based on the conclusion of PKM activities that it is necessary to carry out leadership training activities for teenagers to improve the performance of mosque teenagers. Leadership must be evaluated, because if the youth organization Masjid Al-Jihad gets an organizational leader who has a leadership spirit, it will be easier to coordinate with all other administrators, the community and the local government to help improve the quality of Masjid Al-Jihad Bandar Baru. It is necessary to form a new board that is active and cares about the progress of the Mosque and has good communication between the administrators and the entire local community. The activities carried out at the Al-Jihad Mosque so far need to be added and innovated to make it more interesting and in particular can become a proselytizing shia for the wider community